The Work of Invisibility: Radiation Hazards and Occupational Health in South African Uranium Production - Hecht, Gabrielle (International labor and working class history, 2012)
This article explores the technopolitical mechanisms by which radiation hazards in South African uranium production were rendered invisible. The occupational health effects of underground uranium mining were deeply contested for decades, all over the world. From the 1950s to the 1990s, the volatile nature of labor relations under apartheid shaped how the South African mining industry responded to the presence of radon gas. With occasional help from state scientists, the industry muffled the political menace of radon gas by making its physical presence difficult to see. Sometimes this invisibility resulted from deliberate decisions, sometimes from structural suppression, sometimes from the tangle of both. This article argues that maintaining radon's invisibility took work.